Cytokines - Behzadi, Payam (IntechOpen, 2020)
The human immune system is a complicated biological network that employs a collection of cells, molecules, and proteins. Cytokines play an important role in regulating the innate and adaptive immune systems by different receptors and signaling pathways. As such, they are also implicated in the occurrence of different disorders and diseases. This book presents a comprehensive overview of immunology, the immune system, and cytokines. Chapters cover such topics as the role and importance of tumor necrosis factor (TNF) in the human body, the association of cytokines with different disorders and diseases, and the role of cytokines in dentistry.